Analisis Portfolio Optimal Pada Beberapa Perusahaan LQ-45 Komparasi Pendekatan Markowits Dan Model Indeks Tunggal - Putri, Dwiana Sanjaya; Muktiadji, Nusa (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
In order to minimize the risk, every investor will diverse their investments in a portfolio. This research will form two portfolios, containing three stocks with the highest return and the lowest risks, and with the dividend for the last five years. The two methods used are Single Index Model and Markowitz. Single Index Model involving market in its process while Markowitz only considering the correlation between each stocks. Later will be shown, that both methods’ results are the same for both returns (Individual stocks and portofolio), and a slightly different result with the portofolio’s risks. This proves that the correlation between stocks are also involving in the market. Alam Sutera Realty (ASRI), AKR Corporindo (AKRA), and Global Mediacom (BMTR) are chosen as they have the highest return since 2010, while Astra Agro Lestari (AALI), Adhi Wijaya (ADHI), and Bank Negara Indonesia (BBNI), are chosen for its lowest risk for the last five years. The portfolio A’s returns, calculated with Markowitz method is 45.7% and the risk is 33.78%, and the single index model results for return is exactly the same, 45.7% while the risk is slightly different, 35.8%. The portfolio B’s return, calculated with Markowitz method is 20.7% and the risk is 27.67%, and the single index model’s result for return is exactly the same, 20.7% while the risk is slightly different, 28.24%.